The Role of Instructional Media in Improving Mathematical Literacy Among Primary School Students: A Systematic Literature Review - Mumun Muntasiroh; Riandi Marisa2; Indra Jaya (Alma Ata University Press, 2026)
Low mathematical literacy among Indonesian students and the diverse use of instructional media in elementary schools indicate the need for a comprehensive synthesis of research related to the effectiveness of instructional media. However, previous studies have focused mainly on specific cases and certain types of media, resulting in a limited understanding of the most effective media in supporting mathematical literacy. Therefore, this study aims to identify, analyze, and synthesize empirical evidence regarding the effectiveness of instructional media in improving mathematical literacy among elementary school students in Indonesia. This study employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 protocol, which includes four stages: identification, screening, eligibility, and inclusion. Data were collected through Google Scholar because this database provides broad coverage of national scientific publications and facilitates the retrieval of studies related to elementary education in Indonesia. The search was conducted using predetermined keywords, and the inclusion criteria covered articles published between 2015–2025 in Sinta 1–3 indexed journals, written by Indonesian authors, focused on elementary education, and discussing instructional media in the context of mathematical literacy. A total of seven Indonesian-language articles published between 2018–2025, predominantly using Research and Development (R&D) and quasi-experimental methods, met the inclusion criteria and were systematically analyzed. The findings indicate that various types of instructional media, including computer-based, audio-visual, graphic, printed, manipulative, and digital game-based media, positively affect students’ mathematical literacy. Synthesized findings show that visual, interactive, and contextual media tend to be more effective in improving reasoning, problem-solving, and the application of mathematical concepts. Among these, audio-visual media, particularly HOTS-based and STEAM-integrated videos, demonstrated the most prominent impact by connecting abstract concepts with real-life situations. In addition, culturally based media and digital games enhanced student engagement and supported meaningful learning experiences